2019
DOI: 10.1007/s11869-019-00707-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of indoor air mycobiota of two locals in a food industry, Cuba

Abstract: The aim of this work was to characterize the air mycobiota of two production plants, one of artisanal chocolate and another of products for special regimes in a food factory in Cuba at different times of the year. The air was sampled during 1 year every 25 days distributed in rainy season and non-rainy. The method proposed by Omeliansky was applied and four bacteriostats were used: chloramphenicol, lactic acid, sodium chloride, and iodized common salt with malt agar extract in Petri dishes exposed for 1 h. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The bacterial and fungal counts in this study were also compared to those for a single-occupant office environment and there were higher populations in the office (bacteria=7.33 c.f.u./plate; fungi=2.33 c.f.u./plate). Furthermore, the counts observed in the laser-processing environments were lower than those reported in a tissue culture laboratory [ 19 ], libraries [ 20, 21 ], other indoor environments [ 22, 23 ] and food production environments [ 24–26 ]. Furthermore, the microbial counts found in this study were lower than those reported in other controlled environments, such as operating theatres (at rest=7.2×10 2 c.f.u./plate and during operation=1.05×10 4 c.f.u./plate) [ 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…The bacterial and fungal counts in this study were also compared to those for a single-occupant office environment and there were higher populations in the office (bacteria=7.33 c.f.u./plate; fungi=2.33 c.f.u./plate). Furthermore, the counts observed in the laser-processing environments were lower than those reported in a tissue culture laboratory [ 19 ], libraries [ 20, 21 ], other indoor environments [ 22, 23 ] and food production environments [ 24–26 ]. Furthermore, the microbial counts found in this study were lower than those reported in other controlled environments, such as operating theatres (at rest=7.2×10 2 c.f.u./plate and during operation=1.05×10 4 c.f.u./plate) [ 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…is becoming standard practice as an approach to the monitoring ganisms. Air monitoring can also be included as part of a hazard trol point (HACCP) system in the food industry [5,18].…”
Section: Methodsmentioning
confidence: 99%
“…Fish is considered a widely produced and commercialized food and an important element of the human diet, as it is of high nutritional quality due to its content of biologically Because bioaerosols are of considerable importance in the food sector, their control is becoming standard practice as an approach to the monitoring of total viable microorganisms. Air monitoring can also be included as part of a hazard analysis and critical control point (HACCP) system in the food industry [5,18].…”
Section: Introductionmentioning
confidence: 99%
“…and Cladosporium cladosporioides Fresen.) were colonies of the most common genera obtained in air quality indoor studies in premises in Havana, Cuba (Anaya et al 2016(Anaya et al , 2019. They were selected considering the growth rate, pigmentation and melanin production.…”
Section: Study Strainsmentioning
confidence: 99%